(untitled) (Faridpur Medical College Journal, 2012)
Femoral shaft fracture is an uncommon birth trauma. Bryant’s Traction followed by spica cast is an acceptable method of treatment of femoral shaft fracture 0-18 month’s age group. Here we treated 30 cases of neonatal femur fracture during birth with only Bryant’s Traction of both legs for 3 weeks in hospital. We retrospectively reviewed all neonatal femur fractures occurred during birth admitted in FMCH during a two and half years period. All patients were followed up monthly for 3 months and 6 monthly for 2 years. All fractures healed satisfactorily clinically and radiographically and with no residual deformity, limb length discrepancy or functional impairment. Parents were highly satisfied with the method and its result. It is very simple method and could be safely carried out. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10290 aridpur Med. Coll. J. 2012;7(1): 10-12